The Effect of Different Seasons and Land Types Towards The Performance of Bali Cattle Production in Southeast Sulawesi - La Wangi; Woro Busono; Moch Nasich (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2017)
The Bali Cattle in Southeast Sulawesi its productivity is influenced by the seasonal environmental conditions. The objective of this study was to analyze the performance production of cows Bali Cattle and its calves that were born on different season (rainy season and dry season) as well as on different types of land. The research methods applied were survey and observation method. The variables being observed follows: body weight (BWT), daily body weight gain (PBBH), body condition score (BCS) and birth weight (BW). Data were analyzed by using the Analysis of Variance (ANOVA) of nested design. The result of the research indicated that the average of body weight, daily body weight gain, BCS and birth weight was higher during the rainy season compared to the dry season. The average of body weight, daily body weight gain, and BCS was higher on paddy field. On the contrary, the birth weight on dry area was higher than it was on wetlands. The average of male cattle birth weight was higher than the average of female cattle. It could be concluded that the cow’s working performance production was affected by the feed consumption and environments (season and the type of land). On the other hand, calf birth weight was affected by sexes, in addition it was also related to cow’s feed intake on late pregnancy phase.